Al-Shlobin’s grammatical opinions in explaining the great introduction to the jussive - حيدر, إيمان; يونس يونس (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Al-Shalubin is one of the scholars of the seventh century AH. He wrote several books in the field of Arabic grammar, in which he relied on the grammarians who preceded him, and on what he studied at the hands of his sheikhs. These works included his grammatical opinions, which agreed with these grammarians in many places, especially the scholars of Basra, with whom he agreed in their grammatical doctrine. In several places, he took an opinion that differed from the opinions of other grammarians. The research was interested in studying Al-Shalubin’s opinions, and it focused on a number of grammatical issues in which he agreed with the opinions of grammarians. This includes its agreement with the grammarians in using the infinitive, the present tense verbs, distinction, declinable letters, etc. While he agreed with the grammarians in part of the adverb, and disagreed with them in the affirmative adverb, the significance of (when), and the addition of (from) and other issues.